“CARA MENCEGAH DAN MENGATASI DAMPAK STUNTING PADA ANAK USIA DINI” (Pengabdian Kepada Masyarakat) - Sulistyorini, Ariani; Muchsin, Enur Nurhayati; Sunaringtyas, Widyasih (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2023)
Child growth and development is an indicator of the nutritional and health status of the population of a region and is an indicator of the quality of human resources. Stunting is a health problem in the world and Indonesia, both in urban and rural areas. Intervention is needed to overcome stunting. Parents have a big role in preventing stunting. Special tricks are needed to overcome the impact of stunting on school-aged children. Community service aims to provide education to parents on how to prevent and overcome the impact of stunting in early childhood. The method of community service is education by giving lectures, questions, and answers and role plays. Implementation on 21 and 24 June 2023 at the Pembina Pare State Kindergarten, Kediri with 65 parents participating. After providing education to teachers and parents, it was found that the knowledge and abilities of 25 parents (38%) were good, 35 parents (55%) were sufficient and 5 parents (7%) were poor in preventing and overcoming the impact of stunting on pre-school children. Some ways to overcome stunting are correcting stunting before the age of 2 years, giving breast milk if it is < 6 months old, arranging the correct breastfeeding position, continuing to give breast milk until the age of 2 years, giving processed animal protein (eggs, fish, chicken, milk) to MPASI after aged 6 months every day, routine immunizations according to schedule, monitor the child's growth and development at the Posyandu, clean and healthy living habits, and use a healthy toilet. Preventing and overcoming the impact of stunting is very necessary so parents must know how to prevent it because stunting that is not handled properly can cause long-term impacts, namely decreasing the cognitive development ability of the child's brain.